Tetris: A Compilation Framework for VQA Applications in Quantum Computing - Jin, Yuwei; Li, Zirui; Hua, Fei; Hao, Tianyi; Zhou, Huiyang; Huang, Yipeng; Zhang, Eddy Z. (2024 ACM/IEEE 51st Annual International Symposium on Computer Architecture (ISCA), 2024)
Quantum computing has shown promise in solving complex problems by leveraging the principles of superposition and entanglement. Variational quantum algorithms (VQA) are a class of algorithms suited for near-term quantum computers due to their modest requirements of qubits and depths of computation. This paper introduces Tetris - a compilation framework for VQA applications on near-term quantum devices. Tetris focuses on reducing two-qubit gates in the compilation process since a two-qubit gate has an order of magnitude more significant error and execution time than a single-qubit gate. Tetris exploits unique opportunities in the circuit synthesis stage often overlooked by the state-of-the-art VQA compilers for reducing the number of two-qubit gates. Tetris comes with a refined IR of Pauli string to express such a two-qubit gate optimization opportunity. Moreover, Tetris is equipped with a fast bridging approach that mitigates the hardware mapping cost. Overall, Tetris demonstrates a reduction of up to 41.3 % in CNOT gate counts, 37.9 % in circuit depth, and \mathbf{4 2. 6 %} in circuit duration for various molecules of different sizes and structures compared with the state-of-the-art approaches. Tetris is open-sourced at this link.